Motion response and energy harvesting of multi-module floating photovoltaics in seas - Zheng, Zhi; Jin, Peng; Huang, Qiang; Zhou, Binzhen; Xiang, Ruoxuan; Zhou, Zhaomin; Huang, Luofeng (Elsevier, 2024)
Floating Photovoltaic (FPV) systems are emerging as a new type of ocean renewable energy, offering advantages such as avoiding land use and promoting power generation efficiency. Providing significant cost-effectiveness for manufacturing, transportation, and installation, FPV systems with modular floating platforms exhibit the potential to replace the conventional large steel-frame one. However, the performance of such multi-floating body structures under wave conditions remain underexplored. In this paper, based on potential flow theory, the motion characteristics and power performance of the proposed FPV array connected by the articulated system are evaluated. The results indicate that the FPV arrays with shorter floating structures exhibit greater pitch motion, especially when the wave condition matches the pitch resonance. For multi-float cases, the articulated system, optimized with appropriate parameters, demonstrates efficacy as attenuators. Additionally, the proposed FPV array has great potential to serve as an infrastructure for integrating solar and wave energy. For a selected offshore site, potential wave energy output from motion attenuators between FPV floaters is assessed together with solar energy output. Overall, this study serves as a valuable reference for the design and optimization of the multi-modules FPV and advances the research on combined solar and wave energy utilization on floating structures.
Keywords: Marine renewable energy; Floating photovoltaic; Ocean engineering; Wave energy converters; Offshore solar-wave combination; 4015 Maritime Engineering; 40 Engineering; 7 Affordable and Clean Energy; 13 Climate Action; Civil Engineering; 4012 Fluid mechanics and thermal engineering